Home economics in an oak gall: behavioural and chemical immune strategies against a fungal pathogen in Temnothorax ant nests - Bordoni, Adele; Matejkova, Zuzana; Chimenti, Lorenzo; Massai, Lorenzo; Perito, Brunella; Dapporto, Leonardo; Turillazzi, Stefano (Naturwissenschaften, 2019)
Nest architecture is a fundamental character shaping immune strategies of social insects. The arboreal ant Temnothorax unifasciatus nests in cavities such as oak galls where the entire colony lives in a unique small chamber. In these conditions, physiological and behavioural strategies likely prevail over compartmentalisation and are presumably tuned with colony size. We designed two experiments to study chemical and behavioural immune strategies against the entomopathogenic fungus Metarhizium anisopliae in colonies of different sizes. First, we compared spore germination and length of germinal tubes inside artificial nests, designed to impede the contact between the ants and the fungus, in colonies of different size. In the absence of direct contact, Temnothorax unifasciatus colonies inhibit fungal growth inside their nests, presumably through volatile compounds. The analysis revealed a positive correlation between fungistatic activity and colony size, indicating that workers of smaller colonies do not invest a higher per capita effort in producing such substances compared to larger colonies. Second, we performed a removal experiment of contaminated and non-contaminated items introduced inside the nests of colonies of different size. Small colonies challenged with contaminated fibres showed an increased removal of all the items (both contaminated and non-contaminated) compared to small colonies challenged with non-contaminated fibres only. Conversely, larger colonies moved items regardless of the presence of the spores inside the nest. Colony size qualitatively affected removal of waste items showing a pathogen elicited reaction in small colonies to optimise the reduced workforce, while the removal behaviour in larger colonies revealed to be expressed constitutively.
Keywords: Behavior, Animal; nádory rostlin; dub (rod); Plant Tumors; zvířata; Quercus; Ants; Population Density; Metarhizium; hustota populace; chování zvířat; Formicidae; Animals